On the Bidimensional Euclidean Space - Vera Saravia, Edgar (2018)
We offer a geometric introduction to the two-dimensional Euclidean Space E2 using both the geometric approach of the affine R-Space and the two-dimensional Geometric Algebra.These notes, intented for university proffessors of physics and mathematics, try to emulate the program developed by Felix Kline in the first decade of the 20th century.